Potential and costs for the production of electrolytic hydrogen in alcohol and sugar cane plants in the central and south regions of Brazil - Rodrigues Halmeman, Maria Cristina [UNESP]; Melegari de Souza, Samuel Nelson; Oyama, Paulo Takashi (Pergamon-Elsevier B.V. Ltd, 2008)
This project verified the potential for the production of hydrogen via water electrolysis by using the exceeding electrical energy resultant from alcohol and sugar plants that use sugar cane bagasse as fuel. The studies were carried out in cogeneration plants authorized by the Electrical Energy National Agency (ANEEL). The processing history of sugar cane considered was based on the 2006/2007 harvests. The total bagasse produced, electrical energy generated and exceeding electrical energy in a year were calculated. It was obtained an average energy consumption value of 5.2 kWh Nm(-3) and the hydrogen production costs regarding the amount of sugar cane processed that ranged from US$ 0.50 to US$ 0.75 Nm(-3). The results pointed that the costs for the production of hydrogen via the bagasse exceeding energy are close to the production costs that use other sources of energy. As the energy generated from the bagasse is a renewable one, this alternative for the production of hydrogen is economical and environmentally viable. (C) 2008 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: Sugar cane bagasse; Cogeneration; Exceeding electrical energy